IMPLEMENTATION OF QUANTUM LEARNING BASED ON AUTHENTIC ASSESSMENT IN LEARNING PROCESS - Abdul Aziz (Universitas Muhammadiyah Semarang, 2018)
The courses in mathematics education courses are quite diverse. There are courses that are pure mathematics and there are courses that are pedagogic. Some causes that cause students less understanding of mathematics material is the role of students in following the learningprocess tend to be passive and the method of learning is still conventional so that students are not optimal in implementing the material that is understood. Active and fun learning method will help the students in understanding the materials taught. This is quite important considering the interactive learning activities with the concept of cooperative learning will be able to encourage students to achieve learning objectives. Quantum Learning is one model of learning that is quite effective in shaping the learning conditions that can meet the needs of students. This method encourages students to beresponsible and responsive and care about their friends. Relate to how to express opinions and appreciate the opinions of others. Development Today's authentic assessment has already shown a positive thing. Some curriculum have implemented such a scoring system. Authentic judgment provides a sense of justice for the object being judged. The process of authentic assessment is comprehensive, integrated and in line with the objectives of the assessment. This assessment indicator covers the details and leads to more complex assessments.Keywords : Quantum Learning, Authentic Assessment